(untitled) - Herrenkohl, Roy C. (Australia, 2007)
Becoming a Team puts the ideas, advice, and tools learners need to be successful in the workplace where employer demands "to work as a team" are intensifying. This text blends the latest research on "teams" with an assortment of assessments and exercises. Roy Herrenkohl’s, teaching experience in Lehigh's Business School’s Executive Education courses led him to develop a text on "Teams" – a text based on student needs and one which has been taught in a variety of subject areas including business and engineering. In addition to teaching, he does research on teamwork and employee empowerment and also program evaluation research assessing the impact of educational, social and industrial training activities. Becoming a Team: Achieving a Goal will be a valuable resource for instructors and learners alike in many arenas in which teamwork is taught and practiced.
Keywords: Teams in the workplace